2021
DOI: 10.1111/jcmm.16561
|View full text |Cite
|
Sign up to set email alerts
|

PR11‐364P22.2/ATF3 protein interaction mediates IL‐1β‐induced catabolic effects in cartilage tissue and chondrocytes

Abstract: Osteoarthritis (OA) is a degenerative joint disease which lacks effective medical treatment due to ill‐defined molecular mechanisms underlying the pathology. Inflammation is a key factor that induces and aggravates OA. Therefore, the current study aims to explore roles of the dysregulated long non‐coding RNAs in the pro‐inflammatory cytokine IL‐1β‐mediated catabolic effects in cartilage tissue and chondrocytes. We identified RP11‐364P22.2 as dysregulated in OA patient‐derived cartilage tissues and highly respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…ATF3 belongs to the ATF/cyclic AMP-responsive element binding (CREB) protein family that exerts its transcriptional inhibition or activation effect through interaction with other ATF/CREB members or TFs or binding to its target genes' promoters [ 16 ]. The abnormal expression and dysfunction of ATF3 could contribute to a series of pathophysiological responses, including cell death, inflammatory response, ECM metabolism disorder, oxidative stress, endoplasmic reticulum stress [ 16 , 42 ], and even diseases, such as osteoarthritis [ 43 45 ], cancer [ 16 ], and cardiovascular diseases [ 42 ]. In chondrocytes, ATF3 was expressed in the nucleus and cytoplasm [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATF3 belongs to the ATF/cyclic AMP-responsive element binding (CREB) protein family that exerts its transcriptional inhibition or activation effect through interaction with other ATF/CREB members or TFs or binding to its target genes' promoters [ 16 ]. The abnormal expression and dysfunction of ATF3 could contribute to a series of pathophysiological responses, including cell death, inflammatory response, ECM metabolism disorder, oxidative stress, endoplasmic reticulum stress [ 16 , 42 ], and even diseases, such as osteoarthritis [ 43 45 ], cancer [ 16 ], and cardiovascular diseases [ 42 ]. In chondrocytes, ATF3 was expressed in the nucleus and cytoplasm [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression and dysfunction of ATF3 could contribute to a series of pathophysiological responses, including cell death, inflammatory response, ECM metabolism disorder, oxidative stress, endoplasmic reticulum stress [ 16 , 42 ], and even diseases, such as osteoarthritis [ 43 45 ], cancer [ 16 ], and cardiovascular diseases [ 42 ]. In chondrocytes, ATF3 was expressed in the nucleus and cytoplasm [ 43 45 ]. Iezaki et al [ 43 ] found that the expression of ATF3 was significantly upregulated in the osteoarthritis cartilage of both mice and humans, and the knockdown of ATF3 in chondrocytes decreased cytokine-induced IL-6 transcription by inhibiting NF- κ B signaling to alleviate the development of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine whether CRISPR-dCasΦ system can upregulate the expression of the genes of interest by fusing the crRNA with lncRNA functional motifs that can bind to transcription activators, we separately inserted the lncRNA motifs that bind to the transcription activators ATF3 41 , MYC 42 , STAT3 43 , and YBX1 44 into the 5′-end of crRNAs to construct a series of transcription activation devices (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…6 Inflammation is a common accompaniment and contributes to the development of OA, characterized by a large number of pro-inflammatory mediators including cytokines including IL-1β and IL-6 and chemokines of innate immune response to joint injuries. 7,8) Pro-inflammatory cytokines such as IL-1β promote progressive degeneration of the articular cartilage through the production of matrix metalloproteinase (MMPs), 9 which degrade extracellular matrix components, including collagen and proteoglycans. 10 IL-1β may also induce other proinflammatory cytokines such as IL-6 and IL-8 expression in chondrocytes and synovial fibroblasts.…”
Section: Introductionmentioning
confidence: 99%